2015
DOI: 10.1002/ejlt.201500196
|View full text |Cite
|
Sign up to set email alerts
|

Hydroformylation of vegetable oils: More than 50 years of technical innovation, successful research, and development

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 52 publications
1
27
0
2
Order By: Relevance
“…On the other hand, the hydroformylation of long-chain alkenes (>10 C), with a C=C bond in a deep internal position (>5 C away), remains poorly documented. While the hydroformylation of this kind of substrate without specific regioselectivities targeted (i.e., via the hydroformylation of both internal and terminal C=C bonds) is quite common [17][18][19][20][21], the more challenging tandem isomerization-hydroformylation for the synthesis of terminal aldehydes remains less-studied. In 2005, Behr and coworkers performed the tandem isomerization-hydroformylation of methyl oleate with a Rh-Biphephos catalyst leading the synthesis of terminal aldehydes remains less-studied.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the hydroformylation of long-chain alkenes (>10 C), with a C=C bond in a deep internal position (>5 C away), remains poorly documented. While the hydroformylation of this kind of substrate without specific regioselectivities targeted (i.e., via the hydroformylation of both internal and terminal C=C bonds) is quite common [17][18][19][20][21], the more challenging tandem isomerization-hydroformylation for the synthesis of terminal aldehydes remains less-studied. In 2005, Behr and coworkers performed the tandem isomerization-hydroformylation of methyl oleate with a Rh-Biphephos catalyst leading the synthesis of terminal aldehydes remains less-studied.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Boerner and co‐workers employed a phosphite ligand in the I‐HF of isomeric n ‐octenes, leading to better linear selectivity (up to 48 % n ‐nonanal) . Thus, a literature survey suggested that both (bis)phosphites and bisphosphine can catalyze isomerizing functionalization reactions of internal alkenes at elevated temperatures (120–140 °C) . Among the long‐chain plant oils, linear selective I‐HF of methyl oleate is found to be catalyzed by bisphosphite ligands of type L1 (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…Most of the reactions on oleochemicals occur at the fatty acid carboxy group and they are comparatively few examples on the alkyl chain. However, the presence of double bond(s) in unsaturated fatty acid derivatives allows the installation of a range of organic functions including aldehyde, epoxide, diol, ketone and diketone, α‐hydroxyketone, carbonate, among others . More importantly, cleavage reactions—mainly using methyl oleate as the archetype—can give access to building‐blocks with higher added value, essentially for surfactants and polymer applications.…”
Section: Introductionmentioning
confidence: 99%